Demographic profile, Oral Health Impact Profile and Dental Anxiety Scale in patients with chronic periodontitis: a case–control study. (30th January 2018) - Levin, Liran; Zini, Avraham; Levine, Jonathan; Weiss, Maor; Lev, Ron; Chebath Taub, Daniella; Hai, Avihai; Almoznino, Galit
Abstract : Objectives: To examine whether dental anxiety (DA) and oral health‐related quality of life (OHRQoL) differ between persons with and those without chronic periodontitis. Methods: One‐hundred patients with chronic periodontitis and 50 age‐ and‐ sex‐matched controls were included. Data were collected on the following: demographics; smoking habits; Numerical Rating Scale (NRS) for dental pain assessment; Corah's Dental Anxiety Scale (DAS); Oral Health Impact Profile 14 (OHIP‐14); Decayed, Missing and Filled Teeth (DMFT) index; Plaque Index (PI); probing depth (PD); bleeding on probing (BOP); and radiographic bone loss. Results: Patients with chronic periodontitis exhibited a significantly higher percentage of high anxiety and phobia compared with subjects in the control group. Furthermore, patients with chronic periodontitis were statistically significantly more likely to consider themselves as suffering from dental anxiety (68.7% vs . 14.3%, P < 0.001) as well as more likely to have fear of receiving dental injections, hearing the dental drill noise and feeling a foreign object in the mouth. Patients with chronic periodontitis exhibited worse OHIP‐14 global scores as well as worse scores in the following individual domains: functional limitation ( P = 0.005); physical disability ( P = 0.003); psychological disability ( P = 0.010); social disability ( P = 0.011); and handicap ( P = 0.012). Conclusions: Compared with controls, patients with chronic periodontitis had higher levels of dental anxiety and worse OHRQoL. It is important to consider dental anxiety and OHRQoL assessment as an integral component of the evaluation of patients with chronic periodontitis. Communication between dental and behavioral health professionals is needed to implement a multidisciplinary team approach involving behavioural and psychological interventions.